PERAN BPS SURABAYA DALAM MENYEDI PERAN BPS SURABAYA DALAM MENYEDIAKAN DATA BERKUALITAS UNTUK PERENCANAAN PEMBANGUNAN KOTA - Firmansyah, Afreza Restu F; Ilham, Ilham (Jurnal Manajemen dan Teknologi Informasi, 2026)
This article discusses the role of BPS Surabaya in providing high-quality data to support urban development planning. As a key statistical institution, BPS plays a strategic role in supplying accurate, reliable, and up-to-date data for decision-making in various sectors. The study examines how BPS Surabaya implements quality standards, utilizes digital tools, and collaborates with stakeholders to improve the accessibility and credibility of statistical data. The method used is a qualitative case study through literature review and documentation analysis at BPS Surabaya. The result shows that data from BPS Surabaya has significantly supported evidence-based policy-making at the city level. The article concludes that strengthening digital infrastructure, public awareness, and inter-agency cooperation are essential for enhancing data quality in the public sector.